RIGHT TO ACCESS TO HEALTHCARE: A FAR-REACHING DREAM OF THE TRIBES IN INDIA - P.S, Swathy; Prof. Dr. B. Venugopal; Aswin S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper is an attempt to understand the nature and scope of the right to access healthcare from the perspective of tribal people in India. The paper is based on a review of the literature published in the last few years. It is mainly focused on the issue of access to healthcare among the tribal community in India. This paper delves into the aspect of tribal development in India, the fate of the right to accessibility to healthcare in the tribal communities. The main findings are as follows. First, there are several reasons for the poor implementation of public healthcare schemes in tribal areas; thereby causing a serious threat to the rights of the individual and the obligation of the State. Second, there is a lack of proper planning associated with the establishment of health centers. Third, the State should address the issue relating to the integrity and accountability of the Public Healthcare System as well as its staff including the doctors. Finally, it is concluded that the implementation of healthcare schemes and policies should be framed consistent with the requirements, lifestyle and by respecting the aspirations of tribal community.